AB0026 Immune Complexes Trigger Differentiation of Human Peripheral Naïve CD4+ T Cells. (9th June 2015) - Chen, C.; Bi, Y.; Moore, T.L.; Chauhan, A.K.
Abstract : Background: T cells contribute to the disease process in systemic lupus erythematosus (SLE) (1-3). IFN-γ is a cytokine produced by the Th1 subset that drives autoimmune pathology (4, 5). IFN-γ produced during Th1 response via autocrine process regulates its own expression and also of the transcriptional regulator T-bet ( Tbx21 ). In an autoimmune pathology, CD4 + T cells are activated in the absence of co-stimulatory CD28 signal. The underlying mechanism of this activation is unknown. We show that engagement of low affinity FcγRIIIa from ligation by immune complexes (ICs) provide a co-stimulatory signal that drive the generation of a high IFN-g producing subset and a Th17 like population. We for the first time establish a role for FcgRIIIa in modulating the adaptive immune response. IFN-γ is a key cytokine that enhance B cell response, activate macrophages, and chromatin remodeling Objectives: To investigate the role of ICs in CD4 + naïve T cells differentiation. Methods: We activated peripheral naïve CD4 + CD45RA + T cells in vitro using ICs purified from SLE plasma. Thereafter, we differentiated these cells in the presence of IL-2 (2 U/ml) and IL-12 (50 U/ml) cytokines. We then examined the production of IFN-γ by flow, and in the culture supernatants. Gene transcripts of ifng and Tbx21 were analyzed using qRT-PCR. IFN pathway genes were analyzed using PCR-array. We further examined the role of ICs in the differentiation Th17 cells, in the presence of IL-1b, IL-6, IL23, and TGFβ-1 cytokines. Results: We show that upon activation by ICs human peripheral CD4 + T-lymphocytes differentiate into a Th1 like cell phenotype that produces high levels of IFN-γ and express T-bet. All five donors analyzed demonstrate increases in ifng and Tbx21 transcripts. IFN pathway genes showed several folds from 3 to 20-fold increase in the transcript's associated with IFN signaling. One donor also showed expression of type 1 IFN transcripts that were further up-regulated from ICs signaling. The presence of type 1-IFN transcripts in CD4 + T cells has not been previously demonstrated. The co-stimulatory signal by ICs was more potent than CD28 for the production of IFN-g. In the Th17 polarizing milieu, three subsets of population was observed, IFN-γ + IL17A -, IFN-γ - IL-17A +, and IFN-γ + IL-17 + . Increase in RORC transcripts were also observed. Conclusions: We for the first time demonstrate a role for FcgRIIIa in the differentiation of the human peripheral naïve CD4 + T cells. ICs by ligating FcgRIIIa generated both Th1 and Th17 like populations, thus suggesting a role in autoimmune pathology. References: Konya C, Paz Z, Tsokos GC. The role of T cells in systemic lupus erythematosus: an update. Current Opinion in Rheumatology, 2014, 26(5): 493-501. Smith-Garvin JE, Koretzky GA, Jordan MS. T cell activation. Annual Review of Immunology, 2009, 27: 591. Crispín JC, Kyttaris VC, Terhorst C, et al. T cells as therapeutic targets in SLE. Nature Reviews Rheumatology, 2010, 6(6): 317-325. Pollard KM, Cauvi DM, Toomey CB, et al. Interferon-γ and systemic autoimmunity. Discov Med. 2013, 16(87):123-31. Lazarevic V, Glimcher LH. T-bet in disease. Nature Immunology, 2011, 12(7): 597-606. Disclosure of Interest: None declared